2020
DOI: 10.1292/jvms.19-0630
|View full text |Cite
|
Sign up to set email alerts
|

Orally administrated D-arginine exhibits higher enrichment in the brain and milk than L-arginine in ICR mice

Abstract: D-Amino acids exert various physiological functions and are widely present in animals. However, they are absorbed to a lesser extent than L-amino acids. Little is known about D-arginine (D-Arg); however, its isomer L-Arg serves as a substrate for several metabolites and exhibits various functions including promotion of growth hormone secretion. Milk is the only nutrient source for infants; it plays an important role during their initial growth and brain development. No studies have evaluated the availability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Nagaoka et al [15] reported that free amino acids in mouse milk were metabolized in the mammary glands, since the activity of L-amino acid oxidase was high. L-Arginine transfer to milk is certainly low [16], but L-ornithine, a metabolite of L-arginine investigated here, seemed to transfer to milk more easily than L-arginine. This is close to the results observed with L-serine [17].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Nagaoka et al [15] reported that free amino acids in mouse milk were metabolized in the mammary glands, since the activity of L-amino acid oxidase was high. L-Arginine transfer to milk is certainly low [16], but L-ornithine, a metabolite of L-arginine investigated here, seemed to transfer to milk more easily than L-arginine. This is close to the results observed with L-serine [17].…”
Section: Discussionmentioning
confidence: 62%
“…Consequently, the content of free amino acids targeted by L-amino acid oxidase was very low in conventional milk [15]. For instance, the L-arginine concentration in the milk showed a meager increase of 5 nmol/mL in the L-arginine administration group, while it was significantly increased by about 150 nmol/mL in the plasma as compared to the control group [16]. On the other hand, although L-serine levels did not change significantly in the plasma of the L-serinetreated group, their levels in maternal milk were high (more than 100 nmol/mL) compared with the control group.…”
Section: Introductionmentioning
confidence: 96%
“…Adding D-arginine to food can effectively improve its water solubility and extend its shelf life [6]. A study in mice has also suggested that D-arginine may be added to milk to enhance infant brain development [7]. With the widespread use of D-arginine in the food and pharmaceutical industries, the market demands for D-arginine have also increased.…”
Section: Introductionmentioning
confidence: 99%